PD measurements, failure analysis, and control in high‐power IGBT modules. Issue 3 (1st September 2018) - Ghassemi, Mona
Abstract : Increased voltage blocking capability and the development of packaging technology for IGBTs can enhance the local electric field that may become large enough to increase partial discharges (PDs) within the module. The study presents a survey on (i) simulation the electric field within an IGBT module; (ii) current standards for evaluation of the insulation systems of IGBTs; (iii) PD detection and localisation methods as well as other diagnostic and quality control test methods about IGBTs; and (iv) various methods for PD control in an IGBT module. The survey shows remarkable technical gaps in all four areas. More sophisticated numerical and theoretical techniques are needed to model complicated geometries, e.g. extremely sharp edges of the copper metallisation and protrusions in the substrate, and composite non‐linear field grading materials. There is no model to take into account defects in the gel and on the ceramic substrate. IEC 61287‐1 cannot sufficiently assess the behaviour of PDs on IGBT module under the actual operating conditions exposing fast rise pulse‐width modulation‐like voltages. There is no agreement on the exact origin and location of PDs in the module with relying on measured phase‐resolved PD patterns. PD control methods using non‐linear grading materials are not mature enough.